Marcas no corpo, marcas na alma : as relações familiares de mulheres HIV positivas, infectadas por seus maridos - Andrade, Betina Barbedo (2007)
The consolidation of AIDS as a chronic disease puts in evidence a lot of biological and psychosocial questions related to the life of the carriers, which are highlighted according to the observation of how much they affect their lives. Among the psychosocial aspects, the relationship of the patient with its family has a special importance, understanding the difficulty that each of them face after the diagnosis. The purpose of this research is: to understand the meaning of being HIV positive and living among family; to learn behaviors, feelings and posture of women HIV positive infected by their partners inside daily life of the family and; to investigate changes in the family relationships of these women. It was carried out a descriptive research with qualitative analysis, developed with eight women HIV positive who had a stable and monogamic relationship and who were infected by their companions. Open interview was used as a strategy to collect data inside the women's houses. Data treatment followed the purpose of content analysis technique, suggested by Minayo (1994). The results were presented in thematic categories which showed: the complexity of emotions of living with AIDS; the importance of social nets of support for the life of the HIV woman and, at last, the care of the daily life for those women. The understanding of the meaning of being HIV positive and how this interfere in the family relationship, bring to the nursing professionals the possibility to find strategies helping the family in the process of confrontation, acceptance and naturalizing the HIV, in a way of reducing the devastation that HIV seropositivity can bring to those families. In public health politics, this research can contribute to the reflection of the need to indicate the psychosocial attendance to the carrier and its family, as well as a strategy of the Family Health Program, the way that reflects the subjective care and propose the investment in the care of the carrier's family as a way of keeping the balance and structure of this supports net (family), essential to the carriers. At last, for academic studies, it gives the reflection of the academic and professional education in Brazil, offering to the labor market, better prepared professionals to work facing the brutal reality of the people who live with HIV/AIDS.